Hyper-IgD syndrome and hereditary periodic fever syndromes - R. Scolozzi; A. Boccafogli; L. Vicentini (PAGEPress Publications, 2004)
Hereditary periodic fever syndromes are a group of systemic disorders characterized by recurrent attacks of systemic inflammation (autoinflammation) without infectious or autoimmune cause. The hyper-IgD syndrome (HIDS) is a rare autosomal recessive inflammatory disorder characterized by recurrent fever, increased serum IgD (normal value < 100 U/ml) and generalized inflammation (lymphadenopathy, arthralgias/arthritis, abdominal complaints, skin rash, and headache). The attacks persist during the entire life although frequency and severity tend to diminish with age. HIDS is caused by specific mutations in the gene encoding mevalonate kinase, resulting in depressed enzymatic activity. At present the therapy for the syndrome is only supportive. Other than HIDS, other hereditary systemic inflammatory disorders have been described: the Familial Mediterranean Fever, the tumour necrosis factor receptor associated periodic syndrome (TRAPS), a disease related to the mutations of one of the TNF receptors, the Familial Cold Urticaria and the Muckle-Wells syndrome. The differential diagnosis with other causes of periodic fever is crucial for assessing appropriate management and treatment.